1997
DOI: 10.1002/jhet.5570340335
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and S‐methylation of 2‐thioxopyrido[3′,2′:4,5]thieno[3,2‐d]‐pyrimidin‐4(3H)‐ones with and without a phase transfer catalyst

Abstract: A number of 2‐thioxopyrido[3′,2′:4,5]thieno[3,2‐H]pyrimdin‐4(3H‐ones (5) have been synthesized by cyclocondensation of 2‐carbethoxy‐3‐amino‐4‐phenyl‐6‐substituted‐thieno[2,3‐b]pyridines (3) with various isothiocyanates. Compounds 5 were S‐methylated routinely and the reactions compared under solid‐liquid phase transfer conditions to obtain 2‐methylthiopyrido[3′,2′:4,5]thieno[3,2‐d]pyrimidin‐4(3H)‐ones (6). The new triheterocyclic pyridothienopyrimidines were prepared with the objective to study their pharmacol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The precipitated product was filtered off, washed with water, dried, and crystallized from ethanol as pale yellow crystals. Yield 82%, m. p. > 300 • C -IR (KBr):ν = 3380 -3285 (NH 2 -5,6,7,8-tetrahydropyrido[4',3':4,5]thieno [2,3-d] [1,3]thiazine-7-carboxylate (6) A suspension of compound 5 (6.0 g, 13 mmol) in 98% sulfuric acid (60 ml) and few drops of water was stirred at 40 -50 • C for 10 h. The resultant clear solution was slowly poured on ice-water and sodium bicarbonate (300 ml). The precipitate was collected, washed with ethanol and dried to give compound 6.…”
Section: E T H O D Bmentioning
confidence: 99%
See 1 more Smart Citation
“…The precipitated product was filtered off, washed with water, dried, and crystallized from ethanol as pale yellow crystals. Yield 82%, m. p. > 300 • C -IR (KBr):ν = 3380 -3285 (NH 2 -5,6,7,8-tetrahydropyrido[4',3':4,5]thieno [2,3-d] [1,3]thiazine-7-carboxylate (6) A suspension of compound 5 (6.0 g, 13 mmol) in 98% sulfuric acid (60 ml) and few drops of water was stirred at 40 -50 • C for 10 h. The resultant clear solution was slowly poured on ice-water and sodium bicarbonate (300 ml). The precipitate was collected, washed with ethanol and dried to give compound 6.…”
Section: E T H O D Bmentioning
confidence: 99%
“…The serotonin neurotransmitter is involved in a number of different physiological functions through its interaction with 14 types of receptors [10]. These are G-protein-coupled receptors, with the exception of the 5-HT 3 , which is a ligand gated-ion channel receptor. 5-HT 3 receptor antagonists, such as ondansetron, granisetron, or tropisetron [11] are used as anti-emetic drugs to prevent vomiting associated with chemotherapy or radiation-induced emesis, but literature studies [12] indicated that they could possess numerous other potential therapeutic applications in the control of pain or in the treatment of psychosis, memory impairment, depression, anxiety, schizophrenia, and drugs abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Few works have been found in which a triazole ring was annellated onto existing pyrrolo [2,3-d]pyrimidines [23][24][25]. Therefore, in continuation of our interest in fused triheterocyclic pyrimidines [26][27][28][29], it was interesting to report the synthesis of 7H-pyrrolo[3,2-e] [1,2,4]triazolo [1,5- …”
Section: Introductionmentioning
confidence: 99%
“…So far, there has not been any report on isomeric conversion in the pyrrolotriazolopyrimidine system. Therefore, in continuation of our interest in fused triheterocyclic pyrimidines [26][27][28][29], it was interesting to report the synthesis of 7H-pyrrolo [3,2- Therefore, in continuation of our interest in fused triheterocyclic pyrimidines [26][27][28][29], it was interesting to report the synthesis of 7H-pyrrolo [3,2- …”
Section: Introductionmentioning
confidence: 99%